Combination therapy of curcumin and fecal microbiota transplant: Potential treatment of polycystic ovarian syndrome. (September 2021) - Corrie, Leander; Gulati, Monica; Vishwas, Sukriti; Kapoor, Bhupinder; Singh, Sachin Kumar; Awasthi, Ankit; Khursheed, Rubiya
Abstract: Polycystic ovarian syndrome (PCOS) is a combination of various symptoms like anovulation, hirsutism, chronic amenorrhea, infertility, obesity and polycystic ovaries. It affects over 7 million women worldwide. The current strategy to treat this disorder is based on the use of drugs that provide symptomatic relief. Most of these, however, exhibit numerous side effects and are not able to ameliorate all the signs and symptoms of PCOS. As dysbiosis is considered as one of the prime underlying causes of PCOS, restoration of eubiosis was considered as a plausible way to treat it. Bacteriotherpeutics like probiotics, synbiotics and even fecal microbiota transplant (FMT) have shown considerable effectiveness in PCOS. Of these baceteriotherapeutic options, FMT is considered to be the most holistic as it encompasses the bacteriome, virome, fungome, archaeome and even parasitome while both probiotics as well as synbiotics mainly comprise bacteria. Repeated FMT, however, is not a pragmatic option because of its inconvenience, lack of standardization, involved risk and scepticism amongst patients and physicians. If the eubiosis ushered by FMT is sustained for a long time, the repeated administrations of FMT can be avoided and maintenance therapy with any agent that can maintain the eubiotic condition can be adopted. Role of curcumin on gut microbiota is widely known. It is largely attributed to the ability of certain microbes to consume polyphenols as substrates and its positive effect on bacterial consumption of nutrients such as sugars. Based on various mechanisms and studies, a new hypothesis is being proposed wherein FMT and curcumin combination is predicted to be an effective and sustained treatment of PCOS with much lower rates of remission.